1983
DOI: 10.1007/bf00378225
|View full text |Cite
|
Sign up to set email alerts
|

The structural complexity of old field vegetation and the recruitment of bird-dispersed plant species

Abstract: The input of bird-disseminated seeds into four old fields of different structural complexity was examined. Seed input was greatest along the edges of fields. Significantly more seeds were found in a 13 year old field that had structurally complex vegetation, than in a 3-year-old field with a single layer of vegetation. The lower input into the latter field was a function of both low fruit availability and low structural complexity of the field. Similarly, more seeds were found in a 2-year-old field which had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
199
1
7

Year Published

1984
1984
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 337 publications
(217 citation statements)
references
References 21 publications
10
199
1
7
Order By: Relevance
“…The perches serve, visually in the landscape, as beacons for resting, foraging and latrine sites, resulting in the nuclear deposition of high diversity seed rain, which also represents a feeding place for granivorous animals. Several authors have previously reported the effect of artificial perches on restoration (McDonnel and Stiles, 1983;Guevara et al, 1986;McClanahan and Wolfe, 1993;Whittaker and Jones, 1994;Holl, 1998Holl, , 1999GalindoGonzales et al, 2000;Shiels and Walker, 2003).…”
Section: Nucleation Techniques Includementioning
confidence: 99%
“…The perches serve, visually in the landscape, as beacons for resting, foraging and latrine sites, resulting in the nuclear deposition of high diversity seed rain, which also represents a feeding place for granivorous animals. Several authors have previously reported the effect of artificial perches on restoration (McDonnel and Stiles, 1983;Guevara et al, 1986;McClanahan and Wolfe, 1993;Whittaker and Jones, 1994;Holl, 1998Holl, , 1999GalindoGonzales et al, 2000;Shiels and Walker, 2003).…”
Section: Nucleation Techniques Includementioning
confidence: 99%
“…Additionally, the structural characteristics of plants that growing in pastures (such as their heights, diameters, crown coverage, and densities) will influence seed dispersal as tall, broad trees can provide shelter, nesting, and foraging sites (McDonnell 1986;Dean et al 1999). Trees with wide and more highly branched crowns promote greater seed abundance beneath them (McDonnell & Stiles 1983;Holl 1998;Cole et al 2010;Derroire et al 2016) and can serve as attractive environments for seed dispersers and will provide the immediate microclimate for seed germination and seedling growth (Belsky et al 1989;Callaway 2007;Derroire et al 2016). Trees with a larger diameters and hollows in their trunks are important for many bird species (Mazurek & Zielinski 2004), and trees with larger diameters have greater crown coverage and more branches, and will produce more flowers and seeds (Chapman et al 1992;Greene & Johnson 1994).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that seed deposition in grassland is limited by a lack of suitable perch sites for dispersal vectors; this may lead to slow colonisation of grassland by forest species. By acting as "recruitment foci", isolated remnant trees (McDonnell & Stiles 1983;Guevara et al 1986) and artificial perches (McClanahan & Wolfe 1987,1993 can increase the input of seeds of late-sucessional, fleshy-fruited species to otherwise homogeneous herbaceous fields.…”
Section: Seed Rainmentioning
confidence: 99%
“…The distribution of bird-disseminated seed rain tends to deviate from the smooth decay curve characteristic of wind-dispersed seeds, and may instead be characterised by distinct peaks where perches such as isolated trees act as nuclei for deposition (McDonnell & Stiles 1983;Debussche & Isenmann 1994). Thus, high densities of bird-dispersed seeds have frequently been observed below post-foraging perch sites, with comparatively few seeds encountered in adjacent areas without perches (Debussche et al 1982;Kollmann & Pirl 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation